Asymmetries and inequalities in the Greek regions - Παντελάδης, Ιωάννης; Τσιάπα, Μαρία (The Greek Review of Social Research, 2012)
In the context of the research in question we investigate the convergence dynamics of the GDP per capita among the Greek prefectures during the period 1981-2008. The findings with respect to the conditional β-convergence and σ-convergence seem to support the existence of spatial convergence clubs with differential structural characteristics that, inter alia, relegate to intensive intra/inter regional inequalities. The period under consideration is very important as to the evolution of the spatial asymmetries associated with the participation of Greece in the European institutions as well as with the dynamics of the European integration that affects asymmetrically the distribution of the economic activities across European space therefore the level and the growth rates of the per capita income.